Kenyamanan Termal pada Kerapatan RTH yang Berbeda ditinjau dari Suhu Udara, Kelembapan Udara, Kecepatan Angin, dan Suhu Permukaan di Street Canyon, Jl. MH Thamrin, Jakarta Pusat - Tarigan, Doksa Safira; Nasrullah, Nizar; Sulistyantara, Bambang (Jurnal Arsitektur Lansekap; Vol. 10, No. 1 April 2024DO - 10.24843/JAL.2024.v10.i01.p12, 2024)
Jl. MH Thamrin is a street canyon area that is experiencing global warming, and has minimal vegetation to shade road users. This study aims to describe attributes of thermal comfort at Street Canyon, Jl. MH Thamrin at different green open space densities. Data collection was carried out by observing for 3 days using a thermohygrometer, anemometer data logger, DJI Thermal Drone, mini weather station. The collected air temperature and humidity data are analyzed by THI. The measurement results showed that air temperature data in non-dense area was higher than dense area, with a total average of 31,12°C and 30,27°C. It is different with the humidity which turns out to be more humid in dense areas (62,69%) than in non-dense areas (62,16%). This difference occurs because trees are able to reduce incoming sunlight thereby creating a humid atmosphere. The magnitude of the wind speed in dense areas is 1,41m/s, while for non-dense areas data is lower, namely 0,99 m/s. Surface temperature data is much hotter than air temperature. The lowest surface temperature in the non-dense area is around 26,95°C, while the highest surface temperature is 39,1°C. Likewise, the dense area segment has a maximum surface temperature of 33,9°C with a minimum surface temperature of 26,1°C. Furthermore, through the THI analysis it is known that the two segments are classified as uncomfortable. The highest THI is in non-dense areas 31°C, and 30,1°C in dense areas. It can be concluded that Street Canyon, Jl. MH Thamrin doesn’t have good thermal comfort in both areas.